2002
DOI: 10.1258/0022215021910979
|View full text |Cite
|
Sign up to set email alerts
|

Management of nasal injuries: a postal questionnaire survey of U.K. ENT consultants

Abstract: Nasal injuries are one of the commonest conditions seen in ENT out-patients. There is no uniform policy or protocol for the management of this condition. A postal questionnaire was sent to all UK-based ENT consultants. The aim of this study was to ascertain current practice in the management of this common problem. We were also interested to know if consultants believed that the septum should be addressed and dealt with at the same time as manipulation to improve cosmetic and functional results. Manipulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…There remains a great deal of conflict between clinicians and institutions regarding optimum timing for nasal fracture manipulation to achieve the best aesthetic and functional outcomes and minimise the need for future corrective surgery . Some studies have reported greater patient satisfaction with earlier reduction and proportionately worse results as the injury‐to‐surgery interval increases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains a great deal of conflict between clinicians and institutions regarding optimum timing for nasal fracture manipulation to achieve the best aesthetic and functional outcomes and minimise the need for future corrective surgery . Some studies have reported greater patient satisfaction with earlier reduction and proportionately worse results as the injury‐to‐surgery interval increases .…”
Section: Discussionmentioning
confidence: 99%
“…Current management convention largely stems from anecdotal reports and dated research, with a paucity of any high level evidence to support it . Additionally, there is no solid consensus between centres or clinicians . Despite this, the dogma surrounding nasal fracture management persists and in our experience, some centres have been known not to offer manipulation to patients whose injuries occurred more than 2 weeks previously.…”
Section: Introductionmentioning
confidence: 99%
“…A postal questionnaire study conducted among UK‐based ENT consultants showed that 55.8% practiced digital pressure under GA with use of septal and nasal forceps if needed. At the time of manipulation, 34.8% would assess septum and consider septoplasty; 25.6% would consider septorhinoplasty; and surprisingly, only 38.2% would arrange routine follow‐up …”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence for the benefit of local anaesthesia (LA), 3–7 nasal fractures are still most commonly reduced under GA 8 . Many factors contribute to this, including lack of familiarity with nasal LA and a lack of trained practitioners at the front line of medicine such as emergency doctors and ear, nose and throat surgeons.…”
Section: Introductionmentioning
confidence: 99%